FINANCIAL INCLUSION AND WOMEN EMPOWERMENT: A GENDER PERSPECTIVE - George, Bincy; Thomachan, K.T. (International Journal of Research -GRANTHAALAYAH, 2018)
This paper examines women empowerment associated with financial inclusion. Financial inclusion is delivery of banking services at an affordable cost to the vast sections of disadvantaged and the low-income groups. The various financial services include access to saving, credit, insurance, bank account etc. The access to financial services helps women in their social and economic development. It is noted that access to financial service through financial inclusion do have impact upon the social and financial empowerment of women leading to their overall empowerment.